Factor Structure of the Ways of Coping Questionnaire in Parkinson's Disease - Corti, E.; Johnson, A.; Gasson, Natalie; Bucks, R.; Thomas, M.; Loftus, A. (2018)
© 2018 Emily J. Corti et al. The Ways of Coping Questionnaire (WCQ) is used extensively in health research, but the measurement properties and suitability of the WCQ for people with Parkinson's disease (PD) have not been psychometrically assessed. If the WCQ does not align with its original 8-factor structure in a PD population, the use of the WCQ subscales may not be appropriate. The present study used confirmatory factor analysis (CFA), exploratory factor analysis (EFA), and multiple-group EFA to determine the ideal factor structure of the WCQ in a PD sample. The original 8 factors of the WCQ were not reproduced. EFA revealed a 6-factor structure, including Distancing, Faith, Avoidance, Seeking Social Support, Planful Problem Solving, and Confrontive coping. As motor symptom severity may impact coping, the stability of the 6-factor structure was examined across motor symptom severity (mild and moderate), remaining consistent. Higher levels of overall motor severity were associated with increased use of faith and avoidance style coping. These findings suggest that the 6-factor structure of the WCQ may be more appropriate for assessing coping styles in PD.